Using Programmable Device Installations to Control Students with Disabilities after Blast Traumatic Brain Injury in 10 Meter Walking Test - Blavt, Oksana; Galamanzhuk, Lesia; Huska, Mykhailo; Iedynak, Gennadii; Pityn, Maryan; Kachurak, Yurii; Faidevych, Volodymyr; Turka, Rostyslav (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to determine the degree of authenticity for the test implemented using a programmable installation for monitoring the functions of functional mobility, gait, and the state of the vestibular apparatus in students with disabilities who have sustained a blast traumatic brain injury. Material and methods. The study included a total of 39 first-year students with disabilities after an explosive brain injury. The following methods were used: theoretical analysis of scientific and methodological literature, the method of technical modelling, pedagogical testing, pedagogical experiment, and methods of mathematical statistics. In order to ascertain the efficacy of the proposed intervention, a 10-meter walking test was conducted. Results. The result of our study was the development using information systems and networks of a programmable device for the implementation of the 10-meter walking test, which is used to monitor the recovery of functional mobility, gait, and the state of the vestibular apparatus in students with disabilities after an explosive brain injury. The installation was based on a network of sensors organized according to the Arduino microcontroller platform. Acoustic, optical sensors, distance sensors, proximity sensors, presence sensors, and spatial position sensors have been placed to record the results of the test distance. The sensors, having received an information signal about the student passing the test, transmit it to the controller. In the controller, information is identified, processed, calculated and transferred to a personal computer, where it is displayed on the screen and reproduced graphically. The software ensures maintainability throughout the test, as well as efficiency of data processing, calculation of required parameters and their storage. Data processing is implemented using image analysis systems based on neural networks. According to the findings of testing and correlation analysis, indicators’ authenticity degree for the used tests were established, which differed by the means of measuring the results. The level of correlation coefficient between the values for test reliability and validity in the case of fixing the test results using a stopwatch was not found to fall within the “low” and “acceptable” limits, while in the second case, when the results were fixed by a programmed control unit, it reached the “high” level. Conclusions. The use of the developed programmable device in the practical work of inclusive PE provides convenience, functionality, objectivity and reliability of control in the process of rehabilitation of students with disabilities after an explosive craniocerebral injury. What is confirmed by the values of the test authenticity measure obtained during the experiment when fixing the results by the developed installation.